Desarrollo del análisis foda de la empresa Viteri & Viteri S.A. como herramienta para identificar factores críticos de éxito. - Reyes Ayerves, Richard Bolivar (My University, 2019)
Proper planning is of vital importance when it comes to minimizing risks in the company, for this it is based on an exhaustive analysis of the situation and the environment, which is why it has been proposed as an objective Develop a SWOT analysis by studying the EFI and EFE matrix that identifies the critical success factors of the company Viteri & Viteri, prior to this we proceeded to the collection of bibliographic information of different scientific articles, which served as the basis for the research, followed by the matrix SWOT in order to make the situational diagnosis of the company, and of the matrices of evaluation of internal and external factors (EFI and EFE), in the EFI matrix the weighting was 2.84, which explains that the company remains in the market, having among the factors of greater incidence own shrimp pools, skilled labor and participation and sale of all its production in the market, and Regarding the EFE matrix, the value was 3.01, that is, the strengths and weaknesses of the company have less weight and qualification, the company has opportunities for improvement in internal factors, based on the results obtained it is possible conclude that the tools, SWOT matrix, EFI and EFE, provide business managers with guidelines to follow in order to make timely changes in the company that will make it more competitive in the market.
El presente trabajo de titulación tiene como finalidad el de Desarrollar un análisis FODA mediante el estudio de la matriz EFI y EFE que identifique los factores críticos de éxito de la empresa VITEI & VITERI S.A. La metodología de investigación es de enfoque cualitativo-cuantitativo con método Inductivo- Analítico del tipo descriptivo-explicativo. Las variables de investigación son el análisis FODA (Variable Independiente) y factores críticos de éxito (Variable Dependiente).
Keywords: PLANIFICACIÓN; RIEGOS; DIAGNOSTICO SITUACIONAL; FACTORES INTERNOS; FACTORES EXTERNOS